2008
DOI: 10.1182/blood-2008-02-141614
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide plus dexamethasone is more effective than dexamethasone alone in patients with relapsed or refractory multiple myeloma regardless of prior thalidomide exposure

Abstract: This analysis assessed the efficacy and safety of lenalidomide ؉ dexamethasone in patients with relapsed or refractory multiple myeloma (MM) previously treated with thalidomide. Of 704 patients, 39% were thalidomide exposed. Thalidomideexposed patients had more prior lines of therapy and longer duration of myeloma than thalidomide-naive patients. Lenalidomide ؉ dexamethasone led to higher overall response rate (ORR), longer time to progression (TTP), and progression-free survival (PFS) versus placebo ؉ dexamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(111 citation statements)
references
References 20 publications
5
101
2
3
Order By: Relevance
“…Wang et al 14 reported that efficacy of lenalidomide and dexamethasone was superior to dexamethasone alone in patients with relapsed or refractory MM treated with lenalidomide and dexamethasone regardless of prior thalidomide exposure. The efficacy results were more favorable for patients without than with prior thalidomide treatment; however, this was also observed for patients treated with dexamethasone alone and probably reflects the fact that patients with prior thalidomide exposure were more heavily pretreated (median 3 vs 2 prior therapies).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al 14 reported that efficacy of lenalidomide and dexamethasone was superior to dexamethasone alone in patients with relapsed or refractory MM treated with lenalidomide and dexamethasone regardless of prior thalidomide exposure. The efficacy results were more favorable for patients without than with prior thalidomide treatment; however, this was also observed for patients treated with dexamethasone alone and probably reflects the fact that patients with prior thalidomide exposure were more heavily pretreated (median 3 vs 2 prior therapies).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our results in thalidomide-resistant patients are similar to that of thalidomideresistant patients treated in phase 2 or 3 trials. The median PFS of thalidomide refractory patients in MM009 and MM010 trials was 7 months (95% CI: 4.9-16.9), 26 the median PFS for thalidomide refractory patients in the report by Avet-Loiseau et al 27 was 5.7 months, whereas the median time to progression in immunomodulatory drug refractory patients in the MMY-3001 study was 6 months for patients treated with bortezomib and pegylated liposomal doxorubicin and 5.5 months for those treated with bortezomib alone. 28 It is also interesting that the addition of bortezomib to RD could not overcome the major detrimental effect of previous thalidomide resistance.…”
Section: Discussionmentioning
confidence: 99%
“…60 Patients previously treated with a thalidomide-containing regimen benefit from treatment with lenalidomide, although efficacy and survival may be lower. 61 Because of the lack of neurotoxicity, lenalidomide is suggested in case of concomitant peripheral neuropathy. 60 The second generation proteasome inhibitor carfilzomib has shown a remarkable activity in relapsed/refractory MM patients, with a low rate of hematological AEs and the absence of neurotoxicity.…”
Section: Treatment Strategy At Relapsementioning
confidence: 99%